A dye metallographic etchant and its preparation method and application in quantitative detection of high temperature ferrite in martensitic heat-resistant steel
By using a dyed metallographic corrosion agent containing potassium permanganate, chromic anhydride, perchloric acid and water, the problem of complex and high-cost quantitative detection of high-temperature ferrite in martensite heat-resistant steel is solved, and the microscope is realized It clearly distinguishes and quantitatively detects various organizations, reducing testing costs and simplifying the process flow.
Patent Information
- Application Number
- CN202211057693.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-08-31
AI Technical Summary
The prior art is difficult to effectively detect the content of high-temperature ferrite in martensite heat-resistant steel, and the traditional methods are complex and costly.
Using a dyed metallographic corrosion agent, including potassium permanganate, chromium anhydride, perchloric acid and water, a corrosion agent that can be used at room temperature is prepared through specific ratios and preparation methods, so that martensite can withstand heat. Various tissues in steel exhibit different colors, so that high-temperature ferrite can be clearly distinguished and quantitatively detected under a microscope.
It is possible to clearly distinguish martensite, bainite and high-temperature ferrite under a microscope, and calculate the content of high-temperature ferrite through quantitative metallographic software, which reduces detection costs and simplifies the process flow.
Smart Images

Figure CN115468831B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of quantitative analysis of metallographic microstructures, and in particular relates to a dyeing metallographic corrosive agent and a preparation method thereof, and application thereof in quantitative detection of high-temperature ferrite in martensitic heat-resistant steel. Background Art
[0002] Martensitic heat-resistant steel is mainly used in high temperature and high pressure environments where thermal equipment is operated. It is required to have both high high temperature endurance strength and toughness and certain corrosion resistance. It is widely used in thermal power and nuclear power fields. Its microstructure is composed of martensite or martensite plus bainite (including a small amount of high temperature ferrite), mainly including P92, P91, P122 and other grades. Since there is often a small amount of high temperature ferrite in its structure, high temperature ferrite is produced by the peritectic transformation and precipitation of liquid iron at 1538℃, also known as δ-ferrite. Generally speaking, high temperature ferrite is relatively rare in room temperature environment, but it often exists in some heat-resistant steels. Since high temperature ferrite is a brittle phase, it reduces the toughness of the material, easily causes microcracks during processing, and easily causes pitting corrosion. Therefore, its content is controlled as a harmful phase in martensitic heat-resistant steel.
[0003] The standard YB / T4402-2014 "Metallographic determination of ferrite content in martensitic stainless steel" recommends the use of two metallographic etching solutions (picric acid hydrochloric acid alcohol solution, copper sulfate hydrochloric acid aqueous solution) and two electrolytic etching methods (10% Na (OH) aqueous solution, nitric acid aqueous solution and oxalic acid aqueous solution). In the above methods, high-temperature ferrite generally appears gray, with little difference in contrast with the matrix, and it is impossible to extract color using gray value differences. Only morphology observation can be performed, and then rough quantification can be performed by comparing with the spectrum provided by the standard.
[0004] The Chinese invention patent "A statistical method for the area content of delta ferrite phase in martensitic heat-resistant steel" with publication number CN 103411972A published on November 27, 2013 provides a method for quantifying the high-temperature ferrite by electrolytic etching in a water bath environment to make the high-temperature ferrite black and the matrix white, and using metallographic quantitative software to quantify the high-temperature ferrite. This method requires electrolytic etching, water bath heating during the electrolysis process, complex process and high cost.
[0005] The Chinese invention patent "Method for Determining the Content of δ-Ferrite in 9-12%Cr Martensitic Heat-resistant Steel Welds" with publication number CN103336102A published on October 2, 2013 provides a calculation formula for the high-temperature ferrite content in the weld metal of martensitic heat-resistant steel. However, the contents of 12 elements such as carbon, nitrogen, nickel, and cobalt in the weld metal must be measured first, and then the high-temperature ferrite content must be calculated using regression analysis. This method is complex. Summary of the invention
[0006] The purpose of the present invention is to provide a dyeing metallographic etchant and a preparation method thereof, which uses brand-new raw materials to make various structures in martensitic heat-resistant steel present different colors. Color metallography is also called thin film dyeing method. This method uses a special etchant to react chemically with various phases on the grinding surface to form a film (or reaction precipitate) of uneven thickness. Under the irradiation of white light, due to the interference of light, each phase presents different contrast, thereby improving the ability to distinguish various phases in metals and alloys.
[0007] Another object of the present invention is to provide an application of a dye metallographic etchant in the quantitative detection of high-temperature ferrite in martensitic heat-resistant steel, so that the high-temperature ferrite, martensite and bainite in the martensitic heat-resistant steel appear in different colors under the microscope eyepiece, so that the distribution and morphology of various tissues can be clearly observed, and then the high-temperature ferrite content can be further determined by quantitative metallography.
[0008] The specific technical solutions of the present invention are as follows:
[0009] A dye metallographic etchant comprising potassium permanganate, chromic anhydride, perchloric acid and water.
[0010] The mass ratio of potassium permanganate, chromic anhydride and water is: 3-6:8-10:100;
[0011] The volume ratio of the perchloric acid to water is 1-3:100.
[0012] The water is distilled water.
[0013] The pH value of the dyeing metallographic etching agent is 4-5.
[0014] The present invention provides a method for preparing a dyeing metallographic etching agent, which specifically comprises:
[0015] Mix potassium permanganate, chromic anhydride, perchloric acid and water in the appropriate ratio by mass and let it stand.
[0016] The standing time is 55-65 minutes;
[0017] The above preparation method is carried out at a temperature of 23°C-28°C. The preparation of the present invention can be carried out at room temperature, does not require strict temperature control, and has low cost.
[0018] The application of the dye metallographic etchant provided by the present invention in the quantitative detection of high-temperature ferrite in martensitic heat-resistant steel is specifically described as follows:
[0019] 1) Sample preparation of martensitic heat-resistant steel;
[0020] 2) Pre-corrode the sample with nitric acid, then clean and dry it with anhydrous ethanol;
[0021] 3) immersing the sample treated in step 2) into a dye metallographic etchant with the test surface facing upward;
[0022] 4) After corrosion, observe under a metallographic microscope, high temperature ferrite is white, martensite is brown, bainite is dark blue, and then quantitative phase statistics are performed.
[0023] Step 1) comprises the following steps:
[0024] 1-1) Cut martensitic heat-resistant steel into blocks;
[0025] 1-2) Roughly grind the test surface on a metallographic sample grinder, and then finely grind it with sandpaper;
[0026] 1-3) The ground sample is further polished by mechanical polishing.
[0027] In step 1-1), the specific size of the sample should be suitable for metallographic inspection and observation. Generally, the metallographic inspection surface should be no less than 10mm×10mm. If the sample is too small, the sample should be processed by the inlay method. The microstructural changes caused by temperature increase should be avoided during the sampling process.
[0028] In step 1-2), fine grinding is to use 240#, 600#, and 1000# sandpapers for fine grinding in sequence to remove the wear marks during the rough grinding process. Each time the sandpaper is changed, the grinding is performed perpendicular to the previous wear marks. That is, each time the sandpaper is changed, the sample is rotated 90° so that the wear marks of the previous pass are perpendicular to the wear marks of the current pass. Each pass is ground until the grinding surface is flat, the wear marks are in the same direction, and the wear marks of the previous pass are covered.
[0029] In step 1-3), the polishing is performed by rough polishing and fine polishing with a metallographic polishing agent to remove the scratches and deformation disturbance layer caused by fine grinding, remove the scratches visible to the naked eye, and make the sample surface smooth and flawless. The rough polishing process is to make the test surface lightly pressed on the rotating polishing disk evenly and rotate the polishing direction during polishing. The polishing liquid should be added from time to time during the polishing process while maintaining the appropriate humidity of the polishing surface. The fine polishing process is to continue fine polishing the test surface after the rough polishing to remove fine scratches and deformation layers. After the fine polishing is completed, the surface of the dyed sample is carefully cleaned to make the sample surface clean and free of any oil stains.
[0030] In step 2), the sample treated in step 1) is first pre-corroded with 2-4% nitric acid alcohol by volume for 1-2 seconds, then cleaned with anhydrous ethanol and dried with hot air.
[0031] In step 3), the dried sample is clamped with wooden clips and immersed in the prepared dye metallographic etching agent, with the test surface facing upward so that the color change of the test surface can be seen by the naked eye, and the sample is continuously shaken to make the test surface evenly corroded.
[0032] In step 3), the corrosion time is 40-60s;
[0033] In step 3), based on the formation of an effective thin film interference effect on the surface of the test surface, the corrosion time should be determined by observing the macroscopic color change of the test surface with the naked eye. The color change should be yellow-blue-purple-light brown. The corrosion time should be between 40s and 60s at room temperature. When the color changes to light brown, take out the sample, immediately clean it with anhydrous ethanol and blow dry it with hot air, keep the test surface dry and clean, and do not allow any dirt or water marks.
[0034] The dyeing metallographic etching agent provided by the invention can be recycled and the number of times of use is ≤4 times.
[0035] In step 4), the prepared sample is placed under a metallographic microscope for observation, and the appropriate aperture and field of view light bar are adjusted. The focus knob is adjusted to make the image clear. Under the eyepiece, high-temperature ferrite is white, martensite is brown, and bainite is dark blue. Metallographic quantitative statistical software is used, according to the national standard GB / 15749-2008, to extract the test tissue by using the difference in threshold values of different tissues, calculate the high-temperature martensite content, and also calculate the martensite and bainite content.
[0036] The corrosive agent of the present invention can clearly distinguish martensite, bainite and high-temperature ferrite. At the same time, the high-temperature ferrite content in martensitic heat-resistant steel can be measured by quantitative metallography, and the martensite and bainite contents in the steel can also be determined. Different tissues have large color differences and can be clearly distinguished, providing technical support for the optimization of the production process of heat-resistant steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Color metallographic photograph of the corrosion-resistant heat-resistant steel P91 steel sample 1 of the present invention;
[0038] Figure 2 This is a color metallographic photograph of the corrosion-resistant heat-resistant steel P91 steel sample 2 of the present invention; the high-temperature ferrite content is 3.2%, the bainite is 44.7%, and the martensite is 52.1%;
[0039] Figure 3 This is a color metallographic photograph of the corrosion-resistant heat-resistant steel P91 steel sample 3 of the present invention, the high-temperature ferrite content is 5.8%, the bainite is 45.4%, and the martensite is 48.8%. DETAILED DESCRIPTION
[0040] The present invention is further described below by way of examples. The present invention is further described in detail with reference to the accompanying drawings and specific steps, so as to facilitate a clearer understanding of the present invention.
[0041] Example 1
[0042] An application of a dye metallographic corrosive agent in the quantitative detection of high-temperature ferrite in martensitic heat-resistant steel is described. The detection object is martensitic heat-resistant steel P91 (sample 1). The specific application method is as follows:
[0043] 1) The martensitic heat-resistant steel P91 produced in large-scale industrial production was selected as the research object. The heat-resistant steel was cut into blocks. The specific sample size was that the metallographic detection surface should be no less than 10mm×10mm. If the sample is too small, the sample should be processed by the inlay method. Microstructural changes caused by temperature rise should be avoided during sampling; the detection surface was coarsely ground on the metallographic sample grinder, and then 240#, 600#, and 1000# sandpapers were used for fine grinding in turn to remove the wear marks during the coarse grinding process. Each change of sandpaper was perpendicular to the previous wear marks. That is, each time a sandpaper was changed, the sample was turned 90° so that the wear marks of the previous pass were perpendicular to the wear marks of this pass. Each pass of grinding was carried out until the grinding surface was flat, the wear marks were consistent in direction, and the wear marks of the previous pass were covered; the ground sample was polished by mechanical polishing. Polishing uses metallographic polishing agent for rough and fine polishing to remove scratches and deformation disturbance layers caused by fine grinding, remove visible scratches, and make the sample surface smooth and flawless. The rough polishing process is to make the test surface evenly and lightly press on the rotating polishing disc and rotate the polishing direction. The polishing process should be replenished from time to time while maintaining the appropriate humidity of the polishing surface. The fine polishing process is to continue fine polishing on the test surface after rough polishing to remove fine scratches and deformation layers. After fine polishing, carefully clean the surface of the dyed sample to make the sample surface clean and free of any oil stains.
[0044] 2) Pre-etch the polished sample with 4% nitric acid for 2 seconds to activate the test surface, then clean it with anhydrous ethanol and dry it with hot air.
[0045] 3) Clamp the dried sample with wooden clips and immerse it in the dye metallographic etching agent, with the test surface facing up so that the naked eye can see the color change of the test surface, and keep shaking the sample to make the observation surface evenly corroded. The corrosion time should be determined by the color change of the test surface. The correct color change should be yellow-blue-purple-light brown, and the corrosion time is 45s. When the color changes to light brown, take out the sample, immediately clean it with anhydrous ethanol and blow it dry with hot air, keep the test surface dry and clean, and do not allow any dirt or water marks.
[0046] The preparation method of the dyeing metallographic etchant is as follows: 4g potassium permanganate, 9g chromic anhydride, 3ml perchloric acid and 100ml distilled water are mixed at room temperature; the etchant is ensured to have a pH of 4, and the solution is allowed to stand at room temperature for 60 minutes before use. The dyeing metallographic etchant can be recycled and used ≤4 times, and the ambient temperature is within the range of 23°C-28°C.
[0047] 3) Place the prepared sample under a metallographic microscope for observation, and adjust the appropriate aperture and field of view. Adjust the focus knob to make the image clear. Under the eyepiece, high-temperature ferrite is white, martensite is brown, and bainite is dark blue. Use metallographic quantitative statistical software, according to the national standard GB / 15749-2008, and use the difference in threshold values of different tissues to extract the tissue to be tested, and calculate the high-temperature martensite content. In this embodiment, the high-temperature ferrite content of P91 is 3.8%, bainite is 29.3%, and martensite is 66.9%.
[0048] Example 2
[0049] A dye metallographic etchant is used for quantitative detection of high temperature ferrite in martensitic heat-resistant steel. The detection object is martensitic heat-resistant steel P91. The specific preparation method of the dye metallographic etchant is as follows: 3g potassium permanganate, 9.5g chromic anhydride, 2.5ml perchloric acid and 100ml distilled water are mixed at room temperature; the etchant ensures pH = 4. After the solution is prepared, it can be used after standing at room temperature for 60 minutes. The configured ambient temperature is in the range of 23℃-28℃. Test sample 2, the rest is the same as Example 1, and the test results are as follows Figure 2 .
[0050] Example 3
[0051] The invention discloses an application of a dye metallographic etchant in quantitative detection of high temperature ferrite in martensitic heat-resistant steel. The detection object is martensitic heat-resistant steel P91. The specific preparation method of the dye metallographic etchant is as follows: 6g of potassium permanganate, 8.2g of chromic anhydride, 3ml of perchloric acid and 100ml of distilled water are mixed at room temperature; the etchant is ensured to have a pH value of 4. After the solution is prepared, it can be used after standing at room temperature for 60 minutes. The ambient temperature is set in the range of 23°C-28°C. The other parts are the same as those in Example 1. Sample 3 is detected. The detection results are as follows: Figure 3 .
[0052] Comparative Example 1
[0053] The same martensitic heat-resistant steel P91 was treated with the same method and etchant as in Example 1 for 30 seconds. If the etchant is not enough, a complete diffraction film cannot be formed because the etchant cannot fully react with the sample. Under the irradiation of white light from a microscope, various color illusions will be formed, and the colors are different in depth, making it impossible to identify and quantify.
Claims
1. A dyeing metallographic etching agent, characterized in that: The dyeing metallographic etchant comprises potassium permanganate, chromic anhydride, perchloric acid and water; The mass ratio of potassium permanganate, chromic anhydride and water is: 3-6:8-10:100; The volume ratio of perchloric acid to water is 1-3:100; The pH value of the dyeing metallographic etching agent is 4-5.
2. A method for preparing the dyeing metallographic etching agent according to any one of claim 1, characterized in that: The preparation method comprises the following steps: mixing potassium permanganate, chromic anhydride, perchloric acid and water in a mass ratio and allowing the mixture to stand.
3. The preparation method according to claim 2, characterized in that: The standing time is 55-65 minutes.
4. An application of the dye metallographic etching agent according to claim 1 in quantitative detection of high temperature ferrite in martensitic heat-resistant steel, characterized in that: The specific application method is: 1) Sample preparation of martensitic heat-resistant steel; 2) Pre-corrode the sample with nitric acid, then clean and dry it with anhydrous ethanol; 3) immersing the sample treated in step 2) into a dye metallographic etchant with the test surface facing upward; 4) After corrosion, observe under a metallographic microscope, high temperature ferrite is white, martensite is brown, bainite is dark blue, and then quantitative phase statistics are performed.
5. The use according to claim 4, characterized in that: Step 1) comprises the following steps: 1-1) Cut martensitic heat-resistant steel into blocks; 1-2) Roughly grind the test surface on a metallographic sample grinder, and then finely grind it with sandpaper; 1-3) The ground sample is further polished by mechanical polishing.
6. The use according to claim 4 or 5, characterized in that: In step 3), the corrosion time is 40-60s.
7. The use according to claim 4 or 5, characterized in that: The number of recycling uses of the dyeing metallographic etching agent is ≤4 times.
Citation Information
Patent Citations
Method for determination of delta-ferrite content in martensite refractory steel welding seam with 9-12% of Cr
CN103336102A
Counting method of delta ferritic phase area content in Martensite heat resistant steel
CN103411972A
Method for displaying delta ferrite in P91 and P92 steel
CN114018920A